1978
DOI: 10.7567/jjaps.17s2.425
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Effects on the Kα/Kβ Intensity Ratios in Some Transition Elements

Abstract: Kα/Kβ intensity ratios of 54Cr formd by the decay of various 54Mn-labeled manganese compounds are compared with those of vanadium, chromium and manganese compounds excited with X-rays. In all cases the Kα/Kβ intensity ratios are found to depend on the chemical state of an X-ray emitting atom, decreaeasing in general with an increase in the oxidation number of the central metal ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Fig. 4 shows that the data published by Jones and Urch, 53 Tamaki et al 12 and Best 50 agree much better with our data for compounds with larger M-O average bond lengths than those with short bond lengths. I S1 calculated with experimental relative intensities of Torres Deluigi et al 44 and Tirao et al 43 for chromium oxides, and those of Bergmann et al 37 for manganese oxides follow similar exponential trend with the M-O average bond lengths, although their absolute values are systematically larger or smaller than ours.…”
Section: Relative Intensitiessupporting
confidence: 82%
See 2 more Smart Citations
“…Fig. 4 shows that the data published by Jones and Urch, 53 Tamaki et al 12 and Best 50 agree much better with our data for compounds with larger M-O average bond lengths than those with short bond lengths. I S1 calculated with experimental relative intensities of Torres Deluigi et al 44 and Tirao et al 43 for chromium oxides, and those of Bergmann et al 37 for manganese oxides follow similar exponential trend with the M-O average bond lengths, although their absolute values are systematically larger or smaller than ours.…”
Section: Relative Intensitiessupporting
confidence: 82%
“…For example, Chang et al reported 11 Kb/Ka intensity ratio 0.1479 for V metal, 0.1389 for VN, 0.1563 for VC. For V 2 O 5 they reported 0.1517 AE 0.0004, while Tamaki et al 12 reported 0.130.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…One method of introducing inner-shell vacancies is by means of the electron capture (EC) nuclear decay process. This approach has permitted TAMAKI, OMORI and SHIO-KAWA [2][3][4] and LAZZARINI et al [5] to measure large differences in theKß/Ka ratio for several 51 Cr-containing compounds as well as for 5 'Cr-doped solids. SHIOKAWA and coworkers [2] have thus proposed measurement of the Kß/Ka ratio as an "in situ" method for studying annealing reactions of 51 Cr in potassium Chromate.…”
Section: Introductionmentioning
confidence: 99%
“…SHIOKAWA and coworkers [2] have thus proposed measurement of the Kß/Ka ratio as an "in situ" method for studying annealing reactions of 51 Cr in potassium Chromate. However, the Kß/Ka differences between 51 Cr(III) and 51 Cr(VI) containing samples, of particular interest for annealing studies where observation of the overall process 51 Cr(III) -*• S1 Cr(VI) is the principal objective, showed considerable scatter from one solid matrix to another, indicating surprisingly large matrix effects or, possibly, reflecting inadequate self-absorption corrections applied to the (relatively) thick samples used by these authors [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%